Activities of Several Classes of Acyclic Nucleoside Phosphonates against Camelpox Virus Replication in Different Cell Culture Models - Duraffour, Sophie (American Society for Microbiology (ASM), 2007)
Camelpox virus (CMLV) is the closest known virus to variola virus. Here we report on the anti-CMLV activities of several acyclic nucleoside phosphonates (ANPs) related to cidofovir [(S)-1-(3-hydroxy-2-phosphonomethoxypropyl)cytosine (HPMPC; Vistide)] against two CMLV strains, CML1 and CML14. Cytopathic effect (CPE) reduction assays performed with human embryonic lung fibroblast monolayers revealed the selectivities of the first two classes of ANPs (cHPMPA, HPMPDAP, and HPMPO-DAPy) and of the hexadecyloxyethyl ester of 1-{[(5S)-2-hydroxy-2-oxido-1,4,2-dioxaphosphinan-5-yl]methyl}-5-azacytosine (HDE-cHPMP-5-azaC), belonging to the newly synthesized ANPs, which are HPMP derivatives containing a 5-azacytosine moiety. The inhibitory activities of ANPs against both strains were also confirmed with primary human keratinocyte (PHK) monolayers, despite the higher toxicity of those molecules on growing PHKs. Virus yield assays confirmed the anti-CML1 and anti-CML14 efficacies of the compounds selected for the highest potencies in CPE reduction experiments. Ex vivo studies were performed with a 3-dimensional model of human skin, i.e., organotypic epithelial raft cultures of PHKs. It was ascertained by histological evaluation, as well as by virus yield assays, that CMLV replicated in the human skin equivalent. HPMPC and the newly synthesized ANPs proved to be effective at protecting the epithelial cells against CMLV-induced CPE. Moreover, in contrast to the toxicity on PHK monolayers, signs of toxicity in the differentiated epithelium were seen only at high ANP concentrations. Our results demonstrate that compounds belonging to the newly synthesized ANPs, in addition to cidofovir, represent promising candidates for the treatment of poxvirus infections.